Pengaruh Model Pembelajaran Kooperatif Tipe Numbered Head Together Terhadap Hasil Belajar Pembelajaran Tematik Terpadu Siswa Kelas III SD Swasta Supriyadi Medan - Nirmalawati Nirmalawati; Regina Fredika Sipayung (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This study aims to analyse the effect of the NHT type cooperative model on the learning outcomes of integrated thematic learning of third grade students of SD Swasta Supriyadi Medan with a research type of True Experiment Design in the form of Two Group Pretest Postest Design. The sampling technique used was Cluster Random Sampling. The samples in this study were third grade students of SD Swasta Supriyadi Medan III-A as the experimental class and IV-B as the control class totalling 8 students. Based on the research that has been done, it is obtained tcount> ttable, namely 6.08> 1.860 with α = 0.05 which means H0 is rejected, the average learning outcomes measured by postest after learning, namely in the experimental class 80 and control class 70.63. So that Ha is accepted, namely there is an effect of the NHT Type Co-operative learning model on the learning outcomes of integrated thematic learning of third grade students of SD Swasta Supriyadi Medan.